2008
DOI: 10.2217/14622416.9.9.1229
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the UDP-Glucuronosyltransferase 1A1 Gene for the Development of Unconjugated Hyperbilirubinemia in Taiwanese

Abstract: The c.-3279T>G variant is a further factor for the development of hyperbilirubinemia. Our results also demonstrate that possessing the *60/*60 plus *28/*28 diplotype in the UGT1A1 gene is a determinant of relatively higher bilirubin values amongst hyperbilirubinemic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5]. However, such a mutation is often ignored when the UGT1A1 gene is analyzed [5]. Mimura et al [13] analyzed whether the polymorphism c.1091C>T in UGT1 isoforms affects glucuronidation of various drugs and found that the polymorphism in UGT1A resulted in lower activities towards β-estradiol, acetaminophen, propofol, lamotrigine, imipramine and cyproheptadine than the wild-type.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5]. However, such a mutation is often ignored when the UGT1A1 gene is analyzed [5]. Mimura et al [13] analyzed whether the polymorphism c.1091C>T in UGT1 isoforms affects glucuronidation of various drugs and found that the polymorphism in UGT1A resulted in lower activities towards β-estradiol, acetaminophen, propofol, lamotrigine, imipramine and cyproheptadine than the wild-type.…”
Section: Discussionmentioning
confidence: 87%
“…The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5]. However, such a mutation is often ignored when the UGT1A1 gene is analyzed [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the *28 [(TA) 7 TAA] allele accounts for most of the UGT1A1 polymorphisms seen in the literature, and the level of UGT1A1 activity has been the focus of most studies. 7,8 On the other hand, among Asians, the *6 [211G > A] and *27 [686C > A] alleles are more commonly found in comparison with white populations, and the *37 [(TA) 8 TAA] allele is less common except for African populations. 8 In this study, we aimed to clarify the contribution of UGT1A1 polymorphisms to plasma raltegravir concentrations in Asian patients.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that in addition to the TA7 allele, the Ϫ3279G allele has an effect to further lower the UGT1A1 transcription level. The Ϫ3279G allele has been suggested to associate with poor metabolism of bilirubin by UGT1A1 in hyperbilirubinemia and Gilbert's syndrome (Sugatani et al, 2002;Maruo et al, 2004;Huang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%